Aberrant activation of hedgehog signaling promotes cell proliferation via the transcriptional activation of forkhead Box M1 in colorectal cancer cells. Issue 1 (December 2017) - Wang, DeJie; Hu, Guohui; Du, Ying; Zhang, Cheng; Lu, Quqin; Lv, Nonghua; Luo, Shiwen
Abstract Background Recent evidence suggests that the aberrant activation of Hedgehog (Hh) signaling by Gli transcription factors is characteristic of a variety of aggressive human carcinomas, including colorectal cancer (CRC). Forkhead box M1 (FoxM1) controls the expression of a number of cell cycle regulatory proteins, and FoxM1 expression is elevated in a broad range of human malignancies, which suggests that it plays a crucial role in tumorigenesis. However, the mechanisms underlying FoxM1 expression are not fully understood. Here, we aim to further investigate the molecular mechanism by which Gli1 regulates FoxM1 in CRC. Methods Western blotting and immunohistochemistry (IHC) were used to evaluate FoxM1 and Gli1 protein expression, respectively, in CRC tissues and matched adjacent normal mucosa. BrdU (5-bromo-2′-deoxyuridine) and clone formation assays were used to clarify the influence of FoxM1 on CRC cell growth and proliferation. Chromatin immunoprecipitation (ChIP) and luciferase experiments were performed to explore the potential mechanisms by which Gli1 regulates FoxM1. Additionally, the protein and mRNA expression levels of Gli1 and FoxM1 in six CRC cell lines were measured using Western blotting and real-time PCR. Finally, the effect of Hh signaling on the expression of FoxM1 was studied in cell biology experiments, and the effects of Hh signaling activation and FoxM1 inhibition on the distribution of CRC cells among cell cycle phases was assessed by flow cytometry. Results Gli1 and FoxM1 were abnormally elevated in human CRC tissues compared with matched adjacent normal mucosa samples, and FoxM1 is a downstream target gene of the transcription factor Gli1 in CRC and promoted CRC cell growth and proliferation. Moreover, the aberrant activation of Hh signaling promoted CRC cell proliferation by directly binding to the promoter of FoxM1 and transactivating the activity of FoxM1 in CRC cells. Conclusion The dysregulation of the Hh-Gli1-FoxM1 axis is essential for the proliferation and growth of human CRC cells and offers a potent target for therapeutic intervention in CRC.